Financial Inclusion and Poverty Alleviation in Rejang Lebong Regency - Istan, Muhammad; Asnamawati, Lina; Berlian, Mery (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2019)
Financial inclusion is a condition of products or services from formal financial institutions that can be accessed and relished by various groups of society. Inclusive financial conditions can propel economic growths of the poor through formal financial institutions by forming business groups in each village. This article aims to address how the implementation of financial inclusion programs as a form of concrete efforts in the context of alleviating poverty in Rejang Lebong Regency. Moreover, this study uses a qualitative analysis method with a non-parametric qualitative approach. It shows that the presence of a financial inclusion programs in Rejang Lebong Regency can reduce the poverty level. This poverty alleviation effort is carried out through the pattern of providing venture capital to each Joint Business Group (KUBE) by raising regional superior products as its business, so as it can improve the economy of the local community. The distribution of venture capital assistance is also provided to Small and Medium-Sized Enterprises (UMKM) and religious organizations by maximizing the role and function of the Zakat Collecting Unit (UPZ) in each mosque for productive activities. Therefore, it is necessary to facilitate the granting of permits for the establishment of microfinance institutions such as Islamic cooperatives and savings and loan cooperatives as well as the synergy between the government, Islamic scholars, and the community in order to alleviate poverty through financial inclusion programs. Inklusi keuangan merupakan suatu kondisi produk atau jasa dari lembaga keuangan formal yang dapat diakses dan dinikmati oleh berbagai kalangan masyarakat. Kondisi keuangan yang inklusif dapat mendorong pertumbuhan ekonomi masyarakat miskin melalui lembaga keuangan formal dengan membentuk kelompok usaha disetiap desa. Tulisan ini ingin menjawab bagaimana implementasi program inklusi keuangan sebagai bentuk upaya konkrit dalam rangka mengentaskan kemiskinan di kabupaten Rejang Lebong. Menggunakan metode analisis kualitatif dengan pendekatan kualitatif non parametric, maka dapat disimpulkan bahwa kehadiran program inklusi keuangan di kabupaten Rejang Lebong dapat menurunkan tingkat kemiskinan. Upaya pengentasan kemiskinan ini dilakukan melalui pola pemberian modal usaha kepada setiap Kelompok Usaha Bersama (KUBE) dengan mengangkat produk unggulan daerah sebagai usahanya, sehingga bisa meningkatkan perekonomian masyarakat setempat. Penyaluran bantuan modal usaha ini juga diberikan kepada Usaha Mikro Kecil dan Menengah (UMKM) dan organisasi keagamaan dengan memaksimalkan peran dan fungsi Unit Pengumpul Zakat (UPZ) disetiap masjid untuk kegiatan-kegiatan produktif. Oleh sebab itu diperlukan kemudahan dalam pemberian izin pendirian lembaga keuangan mikro seperti koperasi syariah dan koperasi simpan pinjam serta sinergitas antara pemerintah, ulama, dan masyarakat dalam rangka mengentaskan kemiskinan melalui program inklusi keuangan.